2014
DOI: 10.1159/000358825
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Validity of the Identification of Seniors at Risk Screening Tool in a German Emergency Department Setting

Abstract: Background: The identification of patients at high risk for adverse outcomes [death, unplanned readmission to emergency department (ED)/hospital, functional decline] plays an important role in emergency medicine. The Identification of Seniors at Risk (ISAR) instrument is one of the most commonly used and best-validated screening tools. As to the authors' knowledge so far there are no data on any screening tool for the identification of older patients at risk for a negative outcome in Germany. Objectives: To ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 23 publications
1
38
0
3
Order By: Relevance
“…We assumed an incidence poor 30-day outcome of at least 25%. Based on prior research, the ISAR tool should be able to detect this outcome with an AUC of 0.65 24. Under these assumptions, using with 80% power and a significance level of α=5%, the study should be adequately powered to detect an ROC AUC of 0.65 with a 95% CI of ±5%.…”
Section: Methodsmentioning
confidence: 99%
“…We assumed an incidence poor 30-day outcome of at least 25%. Based on prior research, the ISAR tool should be able to detect this outcome with an AUC of 0.65 24. Under these assumptions, using with 80% power and a significance level of α=5%, the study should be adequately powered to detect an ROC AUC of 0.65 with a 95% CI of ±5%.…”
Section: Methodsmentioning
confidence: 99%
“…Some authors have suggested a higher cut-off point, or that consideration as a continuous variable, may facilitate more efficient use of care resources [31]. They suggest a cut-off of 3 as better in terms of discriminative capacity for adverse outcomes [36]. …”
Section: Tools For Identifying Frailty In Older Patients With Ahfmentioning
confidence: 99%
“…To improve the clinical meaningfulness and eventual practical use of the results, we used continuous score as well as cutoffs to identify patients at risk, based on previous works for SilverCode (>11 points) 12 and Walter indicator (>6 points). 11 Top versus other 2 tertiles (>3 points), a cutoff already used in the literature, 13 was used for the ISAR. Data were collected by expert physicians or nurses working in the unit, which were selected, trained, and stable during the study period.…”
Section: Baseline Evaluationmentioning
confidence: 99%